2017
DOI: 10.11613/bm.2017.035
|View full text |Cite
|
Sign up to set email alerts
|

Does recreational scuba diving have clinically significant effect on routine haematological parameters?

Abstract: IntroductionScuba diving represents a combination of exercise and changes in environmental conditions. This study aimed to evaluate changes in haematological parameters after recreational scuba diving in order to identify clinically significant changes.Materials and methodsThe study included males, 17 recreational divers, median age (range) 41 (30-52) years. Blood samples were taken before diving, immediately after diving to 30 meters for 30 minutes, 3 hours and 6 hours after diving. Complete blood counts were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
9
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 26 publications
4
9
1
1
Order By: Relevance
“…Lipid account that erythrocytes and plasma are considered the most sensitive blood fractions for oxidative damage[21] and since we found no difference in plasma TBARS level and also in carbonylated proteins level in either plasma or erythrocytes, peroxidative damage in erythrocytes appears to be the most pronounced response to oxidative stress caused by scuba diving. It is obvious that erythrocyte membranes are the most vulnerable to ROS overproduction, which could be the reason for the decrease of erythrocyte number after diving, reported in our previous work[22]. Taken together, these findings suggest the importance of the depth and duration of hyperbaric exposure, which is reflected in the necessary decompression during ascent, on ROS overproduction and consequential damage.…”
supporting
confidence: 70%
“…Lipid account that erythrocytes and plasma are considered the most sensitive blood fractions for oxidative damage[21] and since we found no difference in plasma TBARS level and also in carbonylated proteins level in either plasma or erythrocytes, peroxidative damage in erythrocytes appears to be the most pronounced response to oxidative stress caused by scuba diving. It is obvious that erythrocyte membranes are the most vulnerable to ROS overproduction, which could be the reason for the decrease of erythrocyte number after diving, reported in our previous work[22]. Taken together, these findings suggest the importance of the depth and duration of hyperbaric exposure, which is reflected in the necessary decompression during ascent, on ROS overproduction and consequential damage.…”
supporting
confidence: 70%
“…Granulocyte increase is often accompanied by a mild increase in monocytes in the inflammatory response ( Natale et al, 2003 ). However, in this study, the mean number of intermediate cells decreased immediately after surfacing, which was inconsistent with Perovic’s study ( Perovic et al, 2017 ). They found that neutrophils increased and monocytes decreased immediately after 30 m-depth compressed-air diving.…”
Section: Discussioncontrasting
confidence: 99%
“…Other studies report the anti- Both profiles caused a reduction in erythrocytes, hematocrit and hemoglobin, with, again, a greater decrease in the results obtained from the Deeper Decompression Profile (Tables 9 and 10), although the post dive results from both profiles do not present significant difference among each other (p-value > 0.05, Figure 13). This result is also in line with other results obtained by research teams working in collaboration with the Laboratory of Energetics and Theoretical Physiology of the University of Sao Paulo and with a study designed to evaluate changes in hematological parameters after SCUBA diving 86 . It could be speculated that one possible explanation for this reduction is eryptosis, a form of programmed cell death undergone by erythrocytes, known to be triggered by oxidative stress, in a mechanism where caspases expressed by erythrocytes are activated, resulting in the erythrocytes being recognized and engulfed by circulating macrophages.…”
Section: Discussionsupporting
confidence: 91%
“…It could be speculated that one possible explanation for this reduction is eryptosis, a form of programmed cell death undergone by erythrocytes, known to be triggered by oxidative stress, in a mechanism where caspases expressed by erythrocytes are activated, resulting in the erythrocytes being recognized and engulfed by circulating macrophages. Since the erythrocyte membranes are very vulnerable to oxidative damage and erythrocytes are unable to repair damaged components as proteins by re-synthesis, they are very sensitive to oxidative stress 86 .…”
Section: Discussionmentioning
confidence: 99%